1999
DOI: 10.1038/sj.bmt.1701615
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord blood transplant from unrelated HLA-mismatched donors in children with high risk leukemia

Abstract: Summary:In the last 3 years, 14 children with high-risk leukemia (11 ALL, 2 AML and 1 CML) underwent cord blood transplantation from unrelated HLA-mismatched donors at a median of 99 days from the start of search. Eight patients were transplanted in second CR, one in accelerated phase, three at relapse and two patients in first CR. Conditioning regimen (fractionated TBI, etoposide, CY and anti-lymphocyte serum) and prophylaxis of GVHD (CsA and 6-methylprednisolone) were identical for all patients. Neutrophils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The pool of potential donors has also recently expanded with the introduction of unrelated donor cord blood transplantation (CBT). [1][2][3][4][5] An unexpected advantage of CBT was the lower risk of acute graft-versus-host disease (GVHD) in comparison to marrow or mobilized peripheral blood stem cell transplantation. 6 This is thought to result from the relative immaturity of the T cells in cord blood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The pool of potential donors has also recently expanded with the introduction of unrelated donor cord blood transplantation (CBT). [1][2][3][4][5] An unexpected advantage of CBT was the lower risk of acute graft-versus-host disease (GVHD) in comparison to marrow or mobilized peripheral blood stem cell transplantation. 6 This is thought to result from the relative immaturity of the T cells in cord blood.…”
mentioning
confidence: 99%
“…7,8 However, the incidence of acute GVHD with CBT from HLA-mismatched unrelated donors remained substantial (38-73%), and the associated treatment-related mortality has limited long-term outcome. [1][2][3][4][5][6] Tacrolimus is an immunosuppressive macrolide lactone that inhibits the effects of calcineurin in the earliest steps of T cell activation, a mechanism of action similar to that of cyclosporine, but the potency of tacrolimus in vitro is more than 100 times that of cyclosporine. 9 This suggested that tacrolimus might be more effective than cyclosporine as GVHD prophylaxis in high-risk settings.…”
mentioning
confidence: 99%
“…Cord blood represents the most recent source of hematopoietic stem cells used in the unrelated transplant setting for patients who lack a related HLA compatible donor. [1][2][3][4][5][6][7][8][9][10][11][12] Two comparative studies have shown that, in children, unrelated cord blood transplant (CBT) is an acceptable alternative to unrelated bone marrow (BM) transplant. 13,14 Furthermore, three recent reports from either multicentric 9 or unicentric 10,12 experiences suggest that CBT could be considered a reasonable alternative also in adults provided that an adequate number of nucleated cells (NC) is infused.…”
Section: Discussionmentioning
confidence: 99%
“…6 Growth factors were not intentionally used in our patients. However, patients with neuthrophil counts o0.2 Â 10 9 /l and marrow cellularity o5% by day 25 after transplant received granulocyte colony-stimulating factor (G-CSF, Lenograstim, Aventis-Pharma) at the dose of 5 mg/kg daily.…”
Section: Supportive Carementioning
confidence: 99%
See 1 more Smart Citation